Branding Strategy and Social Media Marketing on MSME Business Performance: The Mediating Effect of Sales Performance - Nata Kesuma Wijaya; Wahdiyat Moko (Jurnal Ilmiah Manajemen Kesatuan, 2026)
In a competitive business environment, businesses need to implement effective marketing strategies to turn brand strength and digital presence into tangible sales and sustainable growth. This study aims to analyze the influence of branding strategy and social media marketing on business performance with sales performance as a mediating variable in MSMEs clothing traders. The approach used was quantitative with a survey method through the distribution of questionnaires to 275 randomly selected respondents. Data analysis was carried out using Structural Equation Modeling–Partial Least Squares (SEM-PLS) through SmartPLS 3.0 software. The results of the study show that both branding strategy and social media marketing have a positive and significant effect on sales performance. Furthermore, sales performance has been proven to have a dominant influence on business performance and significantly mediates the influence of branding strategy and social media marketing on business performance. These findings confirm that marketing strategies will yield maximum results only if they are able to increase sales in real terms. Therefore, improving sales performance is a key factor in converting brand strength and digital activities into profitability and sustainable business growth for MSMEs.